Closed reduction of ping-pong fracture in a neonate - El Damaty, Ahmed; Jurgowski, David; Unterberg, Andreas (World neurosurgery, 2020)
Ping-pong fracture in neonates is a well-known complication. There have been many reports on methods to achieve closed reduction using a suction technique. Here we describe in detail the steps for such a maneuver and show the favorable cosmetic outcome without the need for surgery. At the start of the video, the technique for closed reduction of ping-pong fracture in neonates is presented in detail. The present child was born full term through a normal delivery without complications. After delivery, a ping-pong fracture was noticed in the left fronto-temporo-parietal region (see Video 1). The tangential views show the fracture was depressed. An ultrasound was done and showed the depressed fracture without evidence of intracranial bleeding. However, a magnetic resonance imaging scan was done to exclude possible associated intracranial injuries. We then planned the trial for closed reduction under general anesthesia to be able to proceed to open reduction in case of failure. The region was shaved and washed using saline solution to aid the airtight seal needed for suction. We used a cup of a breast milk pump connected to our intraoperative suction device using a suction pressure of 70 mm Hg and used the thumb to control or abort the suction whenever needed. The cup was transparent, which gave us the advantage of observing the reduction when it occurs, compared with a ventouse cup, which is not. The successful reduction is associated with hearing a pop sound. Then the suction was aborted and we achieved a full reduction using this closed technique. The images here after reduction show a favorable cosmetic outcome. An ultrasound was done after reduction and 1 day later to exclude any intracranial complications. Images are then shown after 24 hours without recurrence of the deformity and minimal bruising of the scalp because of the suction applied to the skin over the depressed fracture.
Gesehen am 02.11.2020